Seaworthiness - comparison of standards of seaworthiness in relation to the carriage of goods by sea & to marine insurance - Hauptfliesch, Paula (Institute of Marine and Environmental Law, 2024)
At Common Law, every contract of carriage by sea, is subject to an implied undertaking, on the part of the shipowner ( or carrier), to provide a seaworthy vessel . It is , however, submitted that this implied undertaking may be varied or excluded by “clear and unambiguous” terms or words in the contract.